Inhibition of RFX6 Suppresses the Invasive Ability of Tumor Cells Through the Notch Pathway and Affects Tumor Immunity in Hepatocellular Carcinoma - Song, Mu; Kuerban, Mulati; Zhao, Lu; Peng, Xiaolin; Xu, Youqin (Frontiers in Oncology, 2021)
Background The DNA-binding protein RFX6 was overexpressed in hepatocellular carcinoma, and its expression level was correlated with the prognosis and immune cell infiltration in liver hepatocellular carcinoma. However, the mechanism of the abnormal expression and the biological effects of RFX6 in liver cancer remains unknown. Methods To understand the specific expression mechanism of RFX6 in liver cancer, we performed bioinformatic prediction, CHIP-qPCR assay, co-IP, and dual-luciferase assay to assess the regulating mechanism of RFX6. In the meantime, a series of biological experiments in vivo and in vitro were conducted to analyze the biological significance of RFX6 in hepatocellular carcinoma. Results We demonstrated that knockdown of RFX6 in liver cancer cells significantly suppressed the proliferation, migration, and invasion of cancer cells. Moreover, inhibition of RFX6 could affect the immune response of T cells. Among a number of interacting proteins, we revealed that RFX6 directly binds to DTX2, a regulator of the Notch signaling pathway by targeting NOTCH1, and helps in its transcription stability. Furthermore, we discovered that miRNA-542-3p, the expression of which was decreased in hepatocellular carcinoma, was directly involved in the negative regulation of the expression of RFX6. Conclusion In summary, we discovered that the miRNA-542-3p–RFX6–DTX2–NOTCH1 regulatory pathway played significant roles in the tumor progression of liver hepatocellular carcinoma.